Intersectional boundary work in socializing new experts. The case of IPBES. Issue 1 (1st January 2019) - Gustafsson, Karin M.; Berg, Monika; Lidskog, Rolf; Löfmarck, Erik
ABSTRACT: Expert organizations are often described as facilitators of the interactions between science and policy. In managing this boundary, they must also manage other boundaries, such as those between different knowledge systems and between different categories of actors. However, how this intersectional boundary work is performed, and what it implies, is still unexplored territory. Focusing on the Intergovernmental Science-Policy Platform for Biodiversity and Ecosystem Services (IPBES), this study contributes knowledge on the intersectionality of boundary work and how it influences the production of global policy-relevant knowledge. This is done by examining how IPBES socializes junior experts to become senior experts. This socialization process makes a number of norms and ideals visible and enables an analysis of how the know-how of boundary work is passed forward from one generation of experts to the next. The study analyzes three boundaries: between senior and junior experts, between science and policy, and between scientific knowledge and indigenous and local knowledge. The findings show how intersectional boundary work is crucial in the creation of expert organizations and policy-relevant knowledge. In the case of IPBES, this study shows how the institutionalization of the organization unintentionally has created restrictions for the boundary work between different knowledge systems.